Correlation between social status and health in early medieval Dalmatia - Vyroubal, Vlasta (Array, 2020)
The early mediaeval period in Croatia is rarely mentioned in historical sources. The development of society during this period was greatly influenced by formation of communities, within which there were many inequalities. The social group one belonged to and its ordinance were the main factors in the material and spiritual life of mediaeval man. Within Croatia, during the Early Middle Ages the process of social disintegration and the formation of social groups/strata varied from area to area. However, it can be deduced that this process was the quickest and most complete in the most socially-developed area – the Eastern Adriatic coast. The basic hypothesis of this paper is that people who belonged to different social groups also had different living conditions, which was reflected in their health, quality of life and lifespan. An individual's social status was assessed using the archaeological context, i.e. form of burial. The assumption was made that differences in status were reflected in the manner of the burial. The criteria used to determine social status were grave architecture and quantity and quality of grave finds and goods. In order to assess the health of the individuals anthropological methods were used. These methods included the assessment of age and sex, as well as the analyses of pathologies that leave traces on dry bones. Multivariate statistical methods showed that even though there were social inequalities in the early mediaeval society, the individuals belonging to higher-ranking groups had neither better health, nor lived longer. The results of the analyses carried out in the course of this work show that even though social stratification did exist in the early mediaeval society, biological sex was a much more important factor in life expectancy and quality of life than which social group an individual belonged to.